Corroded iron stent increases fibrin deposition and promotes endothelialization after stenting - Yalan Deng; Yanbin Wen; Jun Yin; Jiabing Huang; Rongsen Zhang; Gui Zhang; Dongxu Qiu (Wiley, 2023)
Abstract Poststent restenosis is caused by insufficient endothelialization and is one of the most serious clinical complications of stenting. We observed a rapid endothelialization rate and increased fibrin deposition on the surfaces of the corroded iron stents. Thus, we hypothesized that corroded iron stents would promote endothelialization by increasing fibrin deposition on rough surfaces. To verify this hypothesis, we conducted an arteriovenous shunt experiment to analyze fibrin deposition in the corroded iron stents. We implanted a corroded iron stent in both the carotid and iliac artery bifurcations to elucidate the effects of fibrin deposition on endothelialization. Co‐culture experiments were conducted under dynamic flow conditions to explore the relationship between fibrin deposition and rapid endothelialization. Our findings indicate that, from the generation of corrosion pits, the surface of the corroded iron stent was rough, and numerous fibrils were deposited in the corroded iron stent. Fibrin deposition in corroded iron stents facilitates endothelial cell adhesion and proliferation, which, in turn, promotes endothelialization after stenting. Our study is the first to elucidate the role of iron stent corrosion in endothelialization, pointing to a new direction for preventing clinical complications caused by insufficient endothelialization.